2014
DOI: 10.1002/14651858.cd006744.pub3
|View full text |Cite
|
Sign up to set email alerts
|

The role of alpha blockers prior to removal of urethral catheter for acute urinary retention in men

Abstract: There was some evidence to suggest that alpha blockers increase the success rates of trial without catheter, and the incidence of adverse effects was low. There was some evidence of a decreased incidence of acute urinary retention. The need for further surgery, cost effectiveness and recommended duration of alpha blocker treatment after successful trial without catheter remain unknown as these were not reported by any trial. There is a lack of internationally agreed outcome measures for what constitutes succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
1
26
0
1
Order By: Relevance
“…Of the trials mentioning adverse effects, there was not enough information to detect statistically significant differences between groups and CoE was low. Overall, adverse effect rates were low for both placebo and a1-blockers [20].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Of the trials mentioning adverse effects, there was not enough information to detect statistically significant differences between groups and CoE was low. Overall, adverse effect rates were low for both placebo and a1-blockers [20].…”
Section: Discussionmentioning
confidence: 91%
“…A Cochrane SR assessed the effectiveness of a1-blockers in successful resumption of micturition following removal of urethral catheter after an episode of AUR in men [20]. Nine RCTs were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2 cohorts of AUR patients treated with alfuzosin (5 mg) or placebo, the rate of therapeutic success was 59% and 18%, respectively . A recent Cochrane review has subsequently confirmed the advantages of using alpha‐blockers with TWOC in AUR patients, making this type of treatment one of the most widely used today. According to Guang‐Jun, spontaneous micturition recovery after AUR secondary to BPE occurs in the 38.9% and 56.8% of patients treated with catheterization alone or catheterization and alpha‐blockers, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Addition of adrenoceptor antagonist may be helpful for treatment acute postoperative urinary dysfunction. 13 Alternatively, patients can be considered for treatment with intermittent catheterization. Patients who fail multiple attempts at voiding trials should be considered for discharge with urinary catheterization.…”
Section: Treatment Of Urinary Dysfunctionmentioning
confidence: 99%